STUDENTS' PERCEPTION ON THE INFLUENCE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN SCIENCE TEACHING AND LEARNING (SED209 & SED317) ON THEIR ICT AND TEACHING SKILLS - Aboderin, Olukayode; Bamisile, Oluwatoyosi (International Journal of Online and Distance Learning, 2021)
Purpose: The purpose of this paper was to explore students' perception on the influence of ICT in science teaching and learning (SED 209 and SED 317) on their ICT and teaching skills. Methodology: The study employed a qualitative study design as a means of carrying out the research. The population consisted of all 300 level and graduating students in the Department of Science Education of Adekunle Ajasin University, Akungba-Akoko. Three research questions were designed to guide the study.The sample of the study was made up of 31 respondents from Science Education Department of the University which were selected using purposive sampling technique. Interview schedule was used to collect data from the respondents. Data collected was analyzed using content analysis. Results: Findings revealed that the two ICT courses influence ICT skills of science education students. Findings also revealed that the knowledge gained from the two courses have really influenced students' teaching skills during teaching practice. Unique Contribution to Theory and Practice: Based on the findings of this study, it was recommended that parent should encourage their children to develop their ICT skills before getting admission so as to enhance learning while taking SED 209 and 317. It was also recommended that government should sanction budgets in ICT head available for students to facilitate teaching and learning of science subjects